Job satisfaction of the accredited social health activists in a community development block of Purba Bardhaman district, West Bengal - Chakraborty, Sohanjan; Roy, Rabindranath; Thakur, Rupali P.; Das, Dilip K. (International Journal Of Community Medicine And Public Health, 2019)
Background: Job satisfaction of accredited social health activist (ASHA), a voluntary health worker under national health mission, is not yet documented in many areas of the country. The present study assessed the job satisfaction of ASHA in Bhatar community development block of Purba Bardhaman district, West Bengal. Methods: A cross sectional study was undertaken during September–November 2017 among all the 191 ASHAs in Bhatar block. With prior consent, interviews were conducted using a questionnaire developed based on measures of job satisfaction (MJS) tool. The questionnaire contained total 28 items in six individual facets of satisfaction-personal component, workload, professional support, training, incentive and care providing. Responses for each item were recorded in 3-point Likert’s scale, total score ranging from 28–84. Overall satisfaction was categorised as dissatisfied (score=28), neutral (29-56) and satisfied (57-84) and similar categorisation was done for individual facets. Chi square test was applied to determine associated factors. Results: Overall 93.7% ASHAs were satisfied with their work, 6.3% were neither dissatisfied nor satisfied. Majority were satisfied regarding individual facets except incentive; 73.3% were rather dissatisfied. Overall satisfaction was significantly associated with the service duration of ASHA (p=0.001). Conclusions: Overall satisfaction level among ASHAs in the area though are quite high, some individual aspects like incentives needs to be looked into. Further studies will be helpful to delineate many unexplored reasons or aspects which might be necessary for developing strategies.